2021
DOI: 10.1021/acs.est.0c07587
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Endocrine Disturbance, and Immune Interference in Humans Showed Relationships to Serum Bisphenol Concentrations in a Dense Industrial Area

Abstract: Bisphenol A (BPA) analogues, used in a range of products due to health concerns regarding BPA, have emerged as ubiquitous environmental contaminants worldwide. This study aims to evaluate the levels of nine bisphenols (BPs) and eight biomarkers (malondialdehyde, MDA; 8-hydroxy-2′-deoxyguanosine, 8-OHdG; estradiol, E2; follicle-stimulating hormone, FSH; luteinizing hormone, LH; complement compound 3, C3; immunoglobulin M, IgM and c-reaction protein, CRP) in human serum (n = 353) to explore their potential relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 88 publications
2
37
0
Order By: Relevance
“…More importantly, the above impact of BP compounds occurred at levels ranging from 0.1 (or 1) to 100 nM, low enough to fall into the range of the real human plasma levels. 14,69 This finding appears consistent with a recent report that long-term exposure of early transformed human mammary cells to BaP and BPA at a very low concentration (0.1 nM) synergistically enhanced their cancerous phenotype via an AhR/G protein-coupled receptor 30. 70 Moreover, human exposure to BPs is not limited to a single BP compound, while multiple BPs may be present in human bodies; 15 thus, combined effects of BPs, such as BPA, BPF, BPS, and BPAF may lead to amplified effect of BPs.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More importantly, the above impact of BP compounds occurred at levels ranging from 0.1 (or 1) to 100 nM, low enough to fall into the range of the real human plasma levels. 14,69 This finding appears consistent with a recent report that long-term exposure of early transformed human mammary cells to BaP and BPA at a very low concentration (0.1 nM) synergistically enhanced their cancerous phenotype via an AhR/G protein-coupled receptor 30. 70 Moreover, human exposure to BPs is not limited to a single BP compound, while multiple BPs may be present in human bodies; 15 thus, combined effects of BPs, such as BPA, BPF, BPS, and BPAF may lead to amplified effect of BPs.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Contamination of various environmental media, such as open air, soil, water, , and indoor air has also been observed, leading to human exposure by inhalation, ingestion, and dermal contact . For example, the mean level of BPA in blood plasma taken from 153 subjects in Hong Kong was 4.2 nM, with 15 nM as the highest value. , Based on a National Health and Nutrition Examination Survey conducted in the U.S. during 2013–2014, the median levels of urinary BPA, BPF, and BPS in U.S. adults amounted to 5.4, 1.7, and 1.5 nM, respectively, with similar values in U.S. children . In addition, in the serum samples collected from subjects living and working in a dense industrial area in Shenzhen, China, high levels of BPA, BPF, and BPAF were detected, which averaged to 184.5, 28.9, and 5.7 nM, respectively …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study of humans who spend considerable time in dense industrial areas showed that their mean serum concentration of BPFL was 0.578 ng/ml and that serum BPFL was significantly correlated with the levels of the oxidative stress indices MDA and 8-OHdG. Another important finding was that the concentrations of BPFL were higher in males than in females ( Gao et al, 2021 ), which suggests that the effect of BPFL needs to be given more attention. Although the adverse effects of BPFL on the reproductive system of female mammals and the underlying mechanism are well documented, its relationship with the reproductive system of male mammals has not yet been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
“…BPF was reported in human serum with the mean concentrations of 0.48 ng/mL for children and 0.049 ng/mL for adults . Due to its growing exposure to humans, the potential toxic effects of BPF have become a public concern .…”
Section: Introductionmentioning
confidence: 99%